Phytoplankton alpha diversity indices response the trophic state variation in hydrologically connected aquatic habitats in the Harbin Section of the Songhua River - Fanhua Meng (Nature Portfolio, 2020)
Abstract The relationship between biodiversity and ecological functioning is a central issue in freshwater ecology, but how this relationship is influenced by hydrological connectivity stress is still unknown. In this study we analyzed the dynamic of the phytoplankton alpha diversity indices and their relationships with trophic state in two hydrologically connected aquatic habitats (Jinhewan Wetland and Harbin Section of the Songhua River) in the Songhua River Basin in northeast China. We hypothesized that the phytoplankton alpha-diversity indices have the potential to provide a signal linking trophic state variation in hydrologically connected aquatic habitats. Our results showed the Cyanophyta and Bacillariophyta were abundant at most stations. T-test showed that phytoplankton alpha diversity indices varied significantly between rainy season and dry season. Trophic State Index recorded that a meso-trophic to eutrophic states of two connected habits during study period. Multivariate statistical analysis revealed that the dynamic of phytoplankton alpha diversity index was closely associated with trophic states change. Our result indicated that hydrological connectivity is a key factor influenced phytoplankton community assembly. In addition, it is beneficial to develop an integrated approach to appropriately describe and measure the trophic state variations of hydrologically connected aquatic habits in freshwater ecosystem.